FDG uptake of pulmonary lesions in synchronous primary lung cancers and lung metastases - Sebastian Karpinski; Zamzam AL Bimani; Jessica L. Dobson; Wanzhen Zeng (Research in Diagnostic and Interventional Imaging, 2024)
Purpose: In lung cancer patients, the distinction between synchronous primary lung cancer and intrapulmonary metastasis can be challenging. The intensity of FDG uptake in pulmonary lesions has been shown to be potentially useful in classifying synchronous lung cancer. The aim of this retrospective study is to investigate the effectiveness of FDG uptake in differentiating metastases from synchronous primary lesions in the setting of lung cancer. Methods: Consecutive patients with primary lung cancer with two or more malignant lung lesions referred for (18F)-FDG PET-CT imaging between 2010 and 2019 were reviewed and classified into synchronous and metastasis groups. Lesional maximum standardized uptake values (SUVmax), relative differences in SUVmax and SUVmax ratios were calculated and compared using receiver operating characteristic (ROC) curve analysis. Intra-group correlation in SUVmax between lesion pairs was examined using Pearson's and Spearman's correlation analysis. Results: 94 patients were included for analysis, divided into synchronous (n = 62; 68 lesion pairs) and metastasis (n = 32; 33 lesion pairs) groups. The correlation of FDG uptake between lesions in the metastasis group was strong (r = 0.81). A significant difference in mean relative difference in SUVmax (synchronous: 0.50±0.23 metastasis: 0.34±0.17, p = 0.001) and mean SUVmax ratio (synchronous: 2.6 ± 1.7 metastasis: 1.7 ± 0.6, p < 0.001) was observed. ROC analysis revealed a fair AUC (0.71–0.72) for these parameters, with an associated sensitivity of 59 % and specificity of 82 % at optimal cut-off values. Conclusion: Differences in FDG uptake intensity among multiple synchronously presenting malignant nodules may be helpful to distinguish second primary lung tumours from metastatic spread.